MORPHOLOGICAL CHARACTERIZATION OF COFFEE (Coffea arabica L.) LANDRACES AT SEEDLING STAGE COLLECTED FROM GUJI ZONES - Alemu, I. D.; Boke, D. S. (Bangladesh Journal of Plant Breeding and Genetics, 2018)
The present study was aimed to determine genetic diversity of Coffea arabica landraces based on morphological characteristics at seedling stage in Guji zones. Three kebeles and twenty-five farmers’ coffee landraces were selected based on availability of Coffea arabica landraces from each district by the guidance of Developmental Agency in the kebele. Coffea arabica seeds were collected and planted at kercha nursery sub-site in plastic pots arranged on randomized block design. Seedling characteristics were collected from one year old randomly selected four coffee seedlings from each plot. The results showed that there were significant variations (p<0.05) between and within Coffea arabica landraces of the district. The seedling height of Coffea arabica collected from Didiba local was highest (11.25) followed by Sorile local (11.17) whereas Ebala local was the least. Coffea arabica from Diqisa local (5.25) was the highest for leaf height followed by Didiba local (5.13), Harobora (5.00) and Wacufora local (5.00). Similarly, Wacufora local (2.05) and Didiba local (2.53) were the highest in leaf width. The Coffea arabica landrace of Qaqali local (6.25) and Harobora local (5.75) were the highest in number of paired leaves. Correlation between the characteristics of coffee seedling showed that seedling height was high and significantly correlated with leaf width (0.62**), number of paired leaves (0.58**), node number (0.57**) and leaf area (0.64**). Similarly, leaf height was high and significantly correlated with leaf width (0.72**) and leaf area (0.77**). Generally, the increase of leaf height increases the leaf width and leaf area. Existence of morphological variation of Coffea arabica at seedling stage was used to determine Coffea arabica diversity in this study area. Therefore, Coffea arabica landraces having high seedling height, leaf height, number of paired leaves and leaf area should get attention during selection for plantation. Additionally, farmers, conservationists and other concerned bodies should take action to conserve and keep the gene pool of these coffees. As a result, it opens the door for biotechnologists to characterize coffee at molecular level and breeder scan take action on it to release superior coffee varieties.